Large surface profile measurement with instantaneous phase shifting interferometry - Hui, Wei Kee. (2008)
In this research, an optical layout that uses the concept of array of points with a modified Michelson interferometer has been proposed. With this setup, a relatively large surface area can be measured without the need for time consuming scanning. In combination with instantaneous phase shifting arrangement, the system is therefore immune to vibration.